DAMPAK NOMOPHOBIA TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Ramadhani, Ratih Wulan; Rahayu, Ratri; Kuryanto, M. Syafruddin (IKIP Siliwangi Bandung, 2021)
This study aims to determine the impact of nomophobia on student motivation in Dukuh Waringin Village RT 01 RW 02 Dawe District, Kudus Regency. The problem analyzed in this study is related to the impact of nomophobia on studentsâ€™ learning motivation. This study used qualitative methods and there were 15 informants consisting of 5 students, 5 parents, and 5 Â siblings. Data collection techniques in this study used observations, interviews, and documentation to determine the impact of nomophobia on learning motivation. The results of this study are elementary school students who experience nomophobia in the village of Dukuh Waringin RT 01 RW 02 Dawe District, Kudus Regency has low learning motivation. Students' motivation to learn decreased after they often played smartphones.Â